The Palestinian Race Track – Design for Safety and Convenience - Ibrahim Abd-Allatif Khalid; Oday Mahmoud Derbas (My University, 2022)
The transportation sector is specialized in roads and highways, among others. Also, there are many sports cars on the street, which lead to speeding. This may cause accidents and loss of life in some cases. To prevent these things, a suitable place has to be available. Therefore, a race track circuit is provided for that, with the best racing criteria in light of local conditions. Data were collected and analyzed. The Palestinian Motor Sport and Motorcycle Federation (PMSMF) was the main source of the local information. Searching for different criteria and specifications, and regulations, the Federation International Automobile (FIA) was used. Few tracks around the world were reviewed to make the optimum track in Palestine. The data were collected through various possible ways; visits, calls, emails, searching in the federation sites and asking the owners of local tracks or arenas, including race car drivers. Then the analysis begins, to understand the idea and the method of design. The available alternative was studied well to select the Jericho land with a1200 dunums, which is about 10km from al-Karama Bridge. Then the racetrack layouts were placed on the land area by the AutoCAD program. But an issue arises, which is the so many shapes to be studied. Therefore, many alternatives were made and studied, leading to an inner struggle. Of course, this was overcome by comparing all alternatives with each other and coming to a consensus. That was obvious in a project with freedom or allowance from a few points. In the second phase of the graduation project, more details were explored. This starts with the design, then the length and width choices, as it has to be decided according to the land and the nearby roads. After that, there was the shape of the track, entrance, exit, parking lot, the VIP lots, and the building management. The design details include the superelevation and the curves, with the minimum radius. This is envisioned to be a carnival piece of land, as it is more fun and more interesting to visitors. For safety, there are three barriers to holding the car or any pieces to reach the audience, and to prevent any person of the audience to reach the track or even near it. In the case of accidents, there are allocations for an ambulance and firemen on the track. In addition, there are the referees’ stands. A detailed 3-D model was developed using the Race Track Builders and the Asseto Corsa programs showing race track details and saving time for the designer.